Flexible employment as a unidirectional career? Results from field experiments - Elisabeth Boerner; Sabine Boerner (Management Revue, 2009)
Although the number of flexible workers is constantly growing, little is known about career paths built up on flexible employment. In this article, we investigate the chances of former flexible workers to be employed in a permanent full-time position. In two field experiments, we asked for employers' evaluation of applicants with a flexible employment history. Results indicate that former part-time work is in fact perceived as a disadvantage for candidates when applying for a permanent full-time position while other types of flexible work (e.g., fixed term contracts, part-time work, and interorganizational mobility) are not. Implications of these results for individual careers and employers' understanding of personnel are discussed.
Keywords: 650; flexible employment; standard employment; contemporary careers; evaluation of CVs